To empathize with a group or an individual? Investigating the role of cognitive cost and distress in empathy choice - Moche, Hajdi; Noryd, Ulrika; Rydén, Sara; Västfjäll, Daniel (Frontiers in Psychology, 2025)
Why do we feel empathy in certain situations, but not others? Previous research has found that people often avoid empathizing when perceived as costly. This study aims to replicate and extend these findings by investigating whether the choice to empathize differs between a group or an individual. Following the empathy selection task paradigm, participants (N = 296) in a within-subject experiment made a series of free choices (empathy choice) selecting whether to engage in empathy or stay objective concerning a single individual and a group of individuals. They also rated perceived cognitive cost and distress concerning empathizing and staying objective. The results show that participants chose to remain objective more often than empathizing in the individual condition along with rating high levels of cognitive effort and distress. In contrast, participants in the group condition more often chose to empathize despite also rating it as more effortful and distressing. We discuss the importance of contextual factors as a main contributor to the difference in empathy choice between group and individual targets.